“INSIDE” AND “OUTSIDE” SPACE IN THE СONTEXT OF THE PERSIAN POLITENESS SYSTEM TA’ĀROF - Mazepova, O. (Linguistic and Conceptual Worldviews, 2019)
The paper deals with the problem of implementation of the binary opposition “inside-outside” within the scope of ta’ārof, the Persian politeness system, which is deeply involved in all the types of social communication in Iran. Here was analyzed a concept set forth by US anthropologist W. Beeman, who states that communicative behavior of Iranians is regulated by strict diﬀerence between “inside” and “outside” space, which is expressed through stylistically marked means of speech. Also here was determined peculiar correlation between the concepts of “inside/outside” space and “inside/outside” behavior incorporated into Iranian worldview since the ancient times. In the situations, which speaker regards as “outside” (birun / zāher) he chooses a communication style in accordance with require- ments of ta’ārof politeness system, demonstrating diﬀerence in status of the interlocutors. And vice versa, in the situations regarded as “inside” (andarun / bāten) ones, he feels comfortable and relaxed, and uses in his speech expressions demonstrating friendliness and sincerity. Yet, when correlation between two frames of behavior is broken the “outside”-mode communication turns into “inside”, and “inside” – into “outside”-mode communication. “Outside” pattern of communication is useful when applied to the misbehaving persons. Unacceptable behavior of “high-ranking person” could well be moderated by intensifying the strategy of “self-lowering” and “other-rising” towards the counterpart, making use of stylistically based means of speech. It was pointed out to the negative aspect of the Persian politeness system, which allows manipulat- ing interlocutor. Identifying and proper reaction from the side of foreigners to such attempts is one of the most important tasks of intercultural communication with Persian native speakers.